The Application of Transformers with High-Temperature Superconducting Windings Considering the Skin Effect in Mobile Power Supply Systems - Vadim Manusov; Inga Zicmane; Ratmir Galeev; Svetlana Beryozkina; Murodbek Safaraliev (Mathematics)
The active and passive components of transformer electrical equipment have reached their limits regarding modernization and optimization, leading to the implementation of innovative approaches. This is particularly relevant for mobile and autonomous energy complexes due to the introduction of increased frequency, which can be advantageous, especially in geoengineering, where the energy efficiency of electrical equipment is crucial. The new design of transformer equipment utilizing cryogenic technologies incorporates high-temperature superconducting (HTS) windings, a dielectric filler made of liquid nitrogen, and a three-dimensional magnetic system based on amorphous alloys. The finite element method showed that the skin effect does not impact HTS windings compared to conventional designs when the frequency increases. The analysis and synthesis of the parameters of the magnetic system made from amorphous iron and HTS windings in an HTS transformer with a dielectric medium of liquid nitrogen at a temperature of 77 K were performed, significantly reducing the mass and size characteristics of the HTS transformer compared to traditional counterparts while eliminating environmental and fire hazards. Based on these studies, an experimental prototype of an industrial HTS transformer with a capacity of 25 kVA was designed and manufactured.